2018
DOI: 10.3390/antiox7050061
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable By-Products to Fortify Spreadable Cheese

Abstract: In this work, spreadable cheese was enriched with flours from by-products (red and white grape pomace, tomato peel, broccoli, corn bran, and artichokes) as sources of fibres and antioxidant compounds. The physicochemical and the sensory properties of all the cheese samples were analysed. Results revealed that total phenolic content, flavonoids, and antioxidant activity of samples containing grape pomace significantly increased, followed by broccoli, artichoke, corn bran, and tomato peel by-products, compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 24 publications
7
50
0
1
Order By: Relevance
“…Based on the olive content, increase in olive level resulted in a slight TS increase. Furthermore, pH value of FC was 4.43, similar to the results published by Lucera et al (2018), while olives showed larger differences. Sample B had a higher pH value (7.55), opposite to G (3.63).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Based on the olive content, increase in olive level resulted in a slight TS increase. Furthermore, pH value of FC was 4.43, similar to the results published by Lucera et al (2018), while olives showed larger differences. Sample B had a higher pH value (7.55), opposite to G (3.63).…”
Section: Resultssupporting
confidence: 88%
“…The Quantitative Descriptive Analysis (QDA) was applied for SCO sensory evaluation, where following sensory properties attributed to SCO were examined: appearance, taste (saltiness, sourness, bitterness, off-taste), flavour (cheese flavour, olive flavour, flavour harmony), odour (cheese odour, olive odour, off-odour), spreadability and the overall acceptance (Lucera et al, 2018). The procedure was conducted by a trained group of thirteen people (n=13) (eight females and five males, 22-59 years old) using a 10-point scale (0 = none, 10 = extremely strong) in a sensory laboratory equipped according to ISO 8589 (2007).…”
Section: Sensory Analysismentioning
confidence: 99%
“…In the 1990s, these by-products were not considered to be a rich and potential sources of antioxidant compounds but, over the last 20 years, agro-industrial by-products with recognised TAC have been incorporated into a varied number of foods. [62][63][64][65][66][67] Because the research on antioxidants suggested beneficial effects on human health, it moved in a direction that aimed to develop and expand knowledge on the concentrations of antioxidants in food sources: in the 2000s, the era of food antioxidants databases arrived.…”
Section: Development Of Rapid In Vitro Methods For Tac Assessmentmentioning
confidence: 99%
“…The addition of polyphenols to dairy foods other than yogurt and fermented milks has received less attention. Wine pomace byproducts have also been the major source of polyphenols used to formulate cheese [ 53 , 56 , 58 , 59 ] and ice-cream [ 50 ], although other phenol byproduct sources have recently been studied in spreadable cheese (tomato peels, broccoli stems and leaves, corn bran and artichoke external leaves) [ 53 ]. The application of broccoli stems in spreadable cheese is particularly interesting, as it could increase glucosinolate content in the product, which are compounds also associated with beneficial health properties [ 117 ].…”
Section: Approaches In the Application Of Food Byproducts In The Dmentioning
confidence: 99%